Deskryptywność i normatywność – horyzonty dialogicznej wizji człowieka - Glinkowski, Witold P. (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
Question about human is the basic thread of contemporary philosophy of dialogue. It does not cause neither systematic concept of human, nor any system of anthropology (in meaning proposed by twentieth-century initiators), but impacts on marginalization of anthropological imponderabilia. Negatively – it was caused by refusal anthropological projects belonging to philosophical heritage by Philosophers of Dialogue. Positively – it was related to new anthropological perspective formulated by these philosophers. By asking questions about human they amend the old yet still important oppositions: nature versus culture and nature versus history (being variant of this first one). The most essential matter in their perspective is opposition between what belongs to nature (different from biological assumptions) and what is relevant to normative perspective. This suspense between two planes – descriptive and prescriptive – seems to be a consequence of the philosophical assumptions of Philosophers of Dialogue and argument for polifonia of anthropological discourse.